THE DEVELOPMENT OF FREEDOM AS A VALUE IN THE PROCESS OF INDIVIDUALIZATION - Svitlana, Hushchyna (European Scientific Journal, ESJ, 2015)
In the article the development of the value of freedom in European political thought is considered, the stages to its understanding in the context of group and individual rights are analyzed, the process of individualization and its connection with the freedom is revealed